An Ultra-Deep Targeted Sequencing Gene Panel Improves the Prognostic Stratification of Patients With Advanced Oral Cavity Squamous Cell Carcinoma. Issue 8 (February 2016) - Liao, Chun-Ta; Chen, Shu-Jen; Lee, Li-Yu; Hsueh, Chuen; Yang, Lan-Yan; Lin, Chien-Yu; Fan, Kang-Hsing; Wang, Hung-Ming; Ng, Shu-Hang; Lin, Chih-Hung; Tsao, Chung-Kan; Chen, I-How; et al.
Abstract : Abstract: An improved prognostic stratification of patients with oral cavity squamous cell carcinoma (OSCC) and pathologically positive (pN+) nodes is urgently needed. Here, we sought to examine whether an ultra-deep targeted sequencing (UDT-Seq) gene panel may improve the prognostic stratification in this patient group. A mutation-based signature affecting 10 genes (including genetic mutations in 6 oncogenes and 4 tumor suppressor genes) was devised to predict disease-free survival (DFS) in 345 primary tumor specimens obtained from pN+ OSCC patients. Of the 345 patients, 144 were extracapsular spread (ECS)-negative and 201 were ECS-positive. The 5-year locoregional control, distant metastases, disease-free, disease-specific, and overall survival (OS) rates served as outcome measures. The UDT-Seq panel was an independent risk factor (RF) for 5-year locoregional control ( P  = 0.0067), distant metastases ( P  = 0.0001), DFS ( P  < 0.0001), disease-specific survival (DSS, P  < 0.0001), and OS ( P  = 0.0003) in pN+ OSCC patients. The presence of ECS and pT3–4 disease were also independent RFs for DFS, DSS, and OS. A prognostic scoring system was formulated by summing up the significant covariates (UDT-Seq, ECS, pT3–4) separately for each survival endpoint. The presence of a positive UDT-Seq panel (n = 77) significantly improved risk stratification for all the survival endpoints as compared with traditional AJCC staging ( P  < 0.0001). Among ECS-negative patients, those with a UDT-Seq-positive panel (n = 31) had significantly worse DFS ( P  = 0.0005) and DSS ( P  = 0.0002). Among ECS-positive patients, those with a UDT-Seq-positive panel (n = 46) also had significantly worse DFS ( P  = 0.0032) and DSS ( P  = 0.0098). Our UDT-Seq gene panel consisting of clinically actionable genes was significantly associated with patient outcomes and provided better prognostic stratification than traditional AJCC staging. It was also able to predict prognosis in OSCC patients regardless of ECS presence.